PENGARUH PENGAWASAN TERHADAP DISIPLIN KERJA PEGAWAI PADA KANTOR LURAH AIR HITAM SAMARINDA ULU - ., Jesfierly (PREDIKSI, 2012)
ABSTRACTThe purpose of this study was to determine whether the Village of Air Hitam Samarinda Ulu contribute to employee discipline. To get the data the authors conducted a study on Village of Air Hitam of Samarinda Ulu.The results showed that the Office of the Chief of Village of Air Hitam Samrinda Ulu greatly contribute to employee discipline, in the sense that the progress of work discipline employees in the Office of Air Hitam of Samarinda Ulu from year to year change increase.Â  This was followed by supervision in this study serves as a variable because to improve discipline an employee as a result of the variable, then factor surveillance activities employees need to take on the job as desired by the leader of the most important is a good cooperation particularly in the Office of Chief of Air Hitam Samarinda Ulu and remain to be defended.